The numerical solution of certain differential equations occurring in Crocco's theory of the laminar boundary layer - Kirkby, S.; Nonweiler, T. (College of Aeronautics, Cranfield, 1953)
A numerical method is described for the solution of certain differential equations which result from the application of Crocco’s transformation to the laminar boundary layer equations appropriate to high supersonic Mach numbers. (i.e. at hypersonic speeds). Continues …